Peranan Kualitas Pelayanan Terhadap Kepuasan Pelanggan di Indomaret Dadi Kusmayadi - Nur Silviana Putri (Universitas 45 Surabaya, 2024)
This research was conducted to explain, find out and describe the quality of service to customers at Indomaret Dadi Kusmayadi. This research uses a qualitative approach research method with a descriptive approach. Data collection techniques use interviews, observation, and documentation. The data analysis model used by researchers is the interactive model of Miles, Huberman, and Saldana (2014: 12-14). This research shows the results that the quality of service to customers at Indomaret must be further improved, and that improvements need to be made by Indomaret employees in terms of service quality. a) Increasing the comfort of the place in serving customers, b) Providing the best service to customers, c) Carrying out service accurately and quickly, d) And being able to consistently provide good service in accordance with the provisions of the Company's Standard Operating Procedures at Indomaret.